RSSI-based Localization With Minimal Infrastructure Using Multivariate Statistic Techniques - Pflaum, Felix; Erhardt, Stefan; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2017)
In this paper a new approach to localization of mobile nodes in wireless sensor networks is presented which utilizes the measurement of the received signal strength indicator by multiple receivers concentrated in a small area and applies the technique of linear discriminant analysis to the received data. The concept of gathering all receivers at a single spot provides great flexibility, while good spatial resolution is still achieved. This is demonstrated by a test network operating in the sub-GHz-range around 868 MHz.
elib2cris::1512001600,pflaum2017
Keywords: wireless; wsn; lda; statistics; localization